AN IMAGINARY DIALOGUE ON CRITICAL ETHNOACCOUNTING RESEARCH - Sukoharsono, Eko Ganis (Accounting Department,, 2014)
The paper is a response of an imaginary dialogue between Papi and Mami, where they are discussing Critical EthnoAccounting-Research. Its objective is to share on the critical paradigm on ethnography method. It is a critical incest between the two, and it is called critical ethno-accountinggraphy. It provides rich ways to conduct an accounting research. The paper addresses from how to start a critical ethno-accounting-graphy, how is as ethno accountinggrapher, as a fisthand, wilderness of techniques, analysis and writing. Finally some examples on critical ethnoaccounting-graphy research are given.